Student views of the International Baccalaureate learner profile. - Daniels, Ian (2015)
2 Abstract This dissertation describes the findings of an investigation into how students view the International Baccalaureate (IB) Learner Profile. Understanding how students see the profile and how they may apply it to their lives can help IB educators to frame tasks and concepts in ways more applicable to students. The research investigated the developmental process and theoretical underpinnings of the Learner Profile. It was found that the links between the Learner Profile and accepted learning theories are ill-defined, and the importance of referring to student voice had been overlooked. The dissertation concludes that there is a real need for creative learner-centric methods of educational research that provide a platform for student voices to be heard, and their opinions given due consideration. The use of student-produced videos for research purposes is proposed as a novel device that can create a space that motivates students to reflect on an issue in a creative medium.